Impact of Covid-19 pandemic on Hospices (ICoH): Carer Cohort Report (2022)
This report describes the diversity of experiences informal carers for people with life-limiting illnesses who were supported by hospices in the West Midlands during the pandemic. It is one of four cohort reports – the others focus on patients, frontline hospice staff, and senior managers respectively – that form the evidence base for a Policy Report into the impact of Covid-19 on hospices. In these reports we address the nine key themes that were identified as potentially important in our previous collaborative knowledge synthesis (MacArtney et al., 2021) and seek to address some of the policy gaps we identified in our review of recommendations for hospice practice and policy (van Langen-Datta et al., 2022). Together these outputs are the result of an Economic and Social Research Council funded study (grant number: ES/W001837/1). This is one of the first studies to contribute an in-depth exploration of hospice-based experiences of the pandemic to the growing body of knowledge about the effectiveness and effects of changes to hospice services, at regional and national levels in response to Covid-19.The aim of this report is therefore to explore experiences of those informal carers of people with life-limiting conditions and the effects of the Covid-19 pandemic on the care and support they experienced, to identify recommendations for clinical practice and healthcare policy. Drawing on these findings, this report offers recommendations for hospices and clinicians who continue to provide care and support for people with life limiting conditions and those that care them during the ongoing pandemic. These recommendations will also be of interest to local commissioners who will need to work with hospices in their region to ensure informal carers receive the support they need, and national policymakers who will need to ensure the necessary resources and guidance are available.